Żydowska pamięć o Polsce lat 1967–1968. Analiza doświadczeń i emocji na podstawie wybranych wspomnień - Szajda, Marek (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article contains an analysis of experiences and emotions from the 1967–1968 period described in the memoirs of two Jewish inhabitants of Wrocław. Their notes present the reaction to the Israeli victory in Six-Day War and subsequent experiences related to communist propaganda, reaction of the society, dislike they sensed, and finally the anti-Semitic campaign in March 1968.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne